Pentingnya Inovasi Kurikulum Pendidikan Agama Islam di Era 4.0 - Icha Fara Diba; Abdul Muhid (Attanwir : Jurnal Keislaman dan Pendidikan, 2022)
One of the goals of Islamic education is to increase human intelligence and increase the spirituality of each individual. Thus education can improve the quality of life of each individual. One of the problems faced in the world of education is related to the curriculum which is the heart of educational institutions. The curriculum that regulates the course of the education system and as the manager of the education program. So if the curriculum does not have innovations that are in accordance with the challenges of the 4.0 industrial revolution, the resulting learning cannot improve the ability of students to compete in the 4.0 industrial revolution. So, the authors research using the literature review research method which results that the PAI curriculum that can answer the challenges of education in industry 4.0 is an adaptive and responsive PAI curriculum by producing various programs that can support the ability of students to think critically and innovatively, collaborate and have a global perspective.